Analisis Pelaksanaan Penanganan Perdagangan Orang di Kota Palembang - Zuber, Konar; Semil, Nurma; Fauzan, Toni (@-Publik: Jurnal Administrasi Publik, 2021)
The purpose of this study is to find out and analyze the implementation of handling of people trafficking in Palembang City. The problems in the research are the lack of coordination and cooperation between the Government and the community in an effort to help the apparatus for the handling of trafficking in Palembang City and the lack of information on people trafficking syndicates in Palembang City. The data analysis technique used in this research is a qualitative data analysis technique. The results showed that the planning carried out by the relevant agencies on handling handlers was well seen from the existence of a clear and measurable annual plan in accordance with the objectives in handling trafficking. With the establishment of an organization that has competent human resources coordination that will be carried out after the formation of TIM can reduce the number and cases of trafficking in Palembang City this is because all TIM will work in accordance with the main tasks and functions based on their respective divisions. Good driving by carrying out a plan through the stages of socialization and training to all TPPO teams in order to perform the task as well as possible. Supervision based on the evaluation and reporting stage after the establishment of the TPPO team coordination and cooperation of the community and government in efforts to implement the handling of trafficking of people is getting better even though there are some families of victims embarrassed in providing information.